Modeling Inflammation in Autism Spectrum Disorders Using Stem Cells - Freitas, Beatriz C.; Mei, Arianna; Mendes, Ana Paula D.; Beltrão-Braga, Patricia C. B.; Marchetto, Maria Carolina (Frontiers in Pediatrics, 2018)
Recent reports show an increase in the incidence of Autism Spectrum Disorders (ASD) to 1 in every 59 children up to 8 years old in 11 states in North America. Induced pluripotent stem cell (iPSC) technology offers a groundbreaking platform for the study of polygenic neurodevelopmental disorders in live cells. Robust inflammation states and immune system dysfunctions are associated with ASD and several cell types participate on triggering and sustaining these processes. In this review, we will examine the contribution of neuroinflammation to the development of autistic features and discuss potential therapeutic approaches. We will review the available tools, emphasizing stem cell modeling as a technology to investigate the various molecular pathways and different cell types involved in the process of neuroinflammation in ASD.